Predictive models of metabolite concentration for organoid expansion - Ellis, M (2022)
This thesis is motivated by the culture of organoids, specifically developing mathematical models for metabolite transport and organoid growth within a fed-plate bioreactor. The bioreactor of interest is the proprietary CXP1 bioreactor, invented by biotechnology company Cellesce, which consists of a layer of hydrogel over which culture media is flowed. Organoids are embedded within the hydrogel and flow is thought to enhance nutrient delivery to, and facilitate waste removal from, the organoids. A key priority is ensuring uniformity in organoid size and reproducibility; qualities that depends on bioreactor design and operating conditions. We show how mathematical modelling can be used to improve the yield of organoids grown within CXP1, by predicting metabolite concentrations during culture for different operating conditions.